Binge-Watching and Continuation Intention in VoD Services: The Mediating Role of Cliffhangers Among Young Viewers - Firman Fauzi; Agung Hudaya; Dewi Murtiningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The impact of binge watching is an evolving phenomenon affecting consumers' continuation intention on video-on-demand (VOD) platforms, mediated by cliffhangers. This study targets a population of young individuals aged 17-25 years. The research design is quantitative, aiming to demonstrate the cause-and-effect relationship between binge watching and continuation intention, mediated by cliffhangers. The novelty of this research lies in not only examining the direct relationship between binge watching and continuation intention but also investigating the mediating effect of cliffhangers, providing deeper insights into the underlying mechanisms of consumer behavior. Data analysis was conducted using the Smart PLS application, utilizing primary data for the study. The findings indicate that cliffhangers directly have a positive and significant impact on the continuation intention for video-on-demand and also significantly influence binge watching. Additionally, binge watching has a positive and significant effect on the continuation intention for video-on-demand. However, indirect, binge watching has a positive but not significant effect on the continuation intention for video-on-demand when mediated by cliffhangers.